Healing the body politic : El Salvador's popular struggle for health rights--from civil war to neoliberal peace - Smith-Nonini, Sandra C. (Studies in medical anthropology., 2010)
Healing the Body Politic examines the contested place of health and development in El Salvador over the last two decades. It recounts the dramatic story of radical health activism from its origins in liberation theology and guerrilla medicine during the third-world country's twelve-year civil war, through development of a remarkable "popular health system," administered by lay providers in a former war zone controlled by leftist rebels. The ethnography contributes to the integration of medical and political anthropology by bringing the semiotics of health and the body to bear